El Delito de Utilización de Personas para Exhibición Pública con Fines de Naturaleza Sexual, no contiene los elementos suficientes que permitan determinar una correcta sanción - Rodríguez Mejía, Kiara Cecibel (2020)
The purpose of this paper is to analyze article 172 of the Comprehensive Organic Criminal Code, which deals with the crime of public display of persons for purposes of a sexual nature. The crime may reveal the indeterminate nature of the elements of the criminal offence which thereby leads to the violation of the rights of children and adolescents, persons with disabilities and the elderly, all of whom belong to the priority group established in article 35 of the Constitution of the Republic of Ecuador. The violation occurs due to the lack of elements in the determination of the criminal type to be punished in article 172 of the Comprehensive Criminal Code. The public exhibition of persons for sexual purposes is a crime that appeared in 2005 with the reforms to the Penal Code Supplement 147 of January 22, 1971. In this case, the passive subject was an adult, and it was not determined what conduct was of a "sexual nature. In 2014, the Comprehensive Organic Criminal Code contemplated this crime with slight changes, in that the passive subject was a vulnerable group, children, adolescents, the elderly, and persons with disabilities were protected, but the conduct was delimited by determining "public exhibition. In this type of criminal law, there has been no further development in the determination of the crime, and it continues to be unclear what are the conducts of a "sexual nature" and other elements that would make it possible to determine a specific conduct that would be subject to a penalty commensurate with the violation caused. The research carried out addresses different topics that allow the understanding and deepening of the subject matter, as is the case of sexual assault, behaviors that have been present in the life of men, in this work we will analyze some sexual practices that were carried out in antiquity. We will also review in comparative law the criminal 5 types that are appropriate to the crime studied, in which the conduct that is subject to punishment is clearly determined, as well as the modalities in which the crime is presented. We have also carried out field work, carrying out surveys aimed at lawyers in free practice and interviews with the different specialists whose contribution we have considered fundamental.